FEATURES OF PHYSICAL THERAPY AND GLUTEN-FREE DIET IN THE WORK WITH CHILDREN WITH AUTISTIC SPECTRUM DISORDERS - Лістау, Каринга (SWorldJournal, 2023)
Autism spectrum disorder is included in the group of pervasive disorders of mental development. Such children show changes in emotional development, communication and social skills, language and behavior. According to world statistics, an increase in case